Uji Kualitatif Kandungan Formalin Pada Mie Basah di Pasar Induk Jakabaring Palembang Tahun 2026 - Silvia Indra; Riki Rinaldi; Izzatinisa Izzatinisa; Melsya An'nur (JURNAL KESEHATAN TERAPAN, 2026)
Fresh noodles are a staple food widely consumed by Indonesians because they are convenient and readily available. Their high water content makes fresh noodles prone to spoilage, leading to the continued misuse of formalin as an illegal preservative. The use of formalin in food is prohibited because it is toxic and poses a potential health risk to consumers. This study aims to qualitatively identify the presence of formalin in fresh noodles sold at the Jakabaring Central Market in Palembang as an indicator of food safety. The study employed a descriptive laboratory design. The research was conducted on May 25, 2026, using 13 samples of fresh noodles obtained via total sampling from vendors at the Jakabaring Central Market in Palembang. Formalin testing was performed qualitatively using 0.1 N potassium permanganate (KMnO₄) reagent. A sample was considered positive if the purple color of the 0.1 N KMnO₄ solution changed to clear, orange, or brownish-yellow. The data were analyzed descriptively and presented as frequencies and percentages. All wet noodle samples tested showed a color change in the 0.1 N KMnO₄ reagent and were therefore deemed positive for formalin. Of the 13 samples analyzed—with one repeat test conducted—all 13 samples (100%) tested positive for formalin. These findings indicate that food products that do not meet food safety requirements are still in circulation, necessitating increased oversight by relevant agencies as well as education for producers and the public regarding the dangers of using formalin in food.